Plasma PolyQ-ATXN3 Levels Associate With Cerebellar Degeneration and Behavioral Abnormalities in a New AAV-Based SCA3 Mouse Model - Jansen-West, Karen; Todd, Tiffany W.; Daughrity, Lillian M.; Yue, Mei; Tong, Jimei; Carlomagno, Yari; Del Rosso, Giulia; Kurti, Aishe; Jones, Caroline Y.; Dunmore, Judith A.; Castanedes-Casey, Monica; Dickson, Dennis W.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Spinocerebellar ataxia type 3 (SCA3) is a dominantly inherited cerebellar ataxia caused by the expansion of a polyglutamine (polyQ) repeat in the gene encoding ATXN3. The polyQ expansion induces protein inclusion formation in the neurons of patients and results in neuronal degeneration in the cerebellum and other brain regions. We used adeno-associated virus (AAV) technology to develop a new mouse model of SCA3 that recapitulates several features of the human disease, including locomotor defects, cerebellar-specific neuronal loss, polyQ-expanded ATXN3 inclusions, and TDP-43 pathology. We also found that neurofilament light is elevated in the cerebrospinal fluid (CSF) of the SCA3 animals, and the expanded polyQ-ATXN3 protein can be detected in the plasma. Interestingly, the levels of polyQ-ATXN3 in plasma correlated with measures of cerebellar degeneration and locomotor deficits in 6-month-old SCA3 mice, supporting the hypothesis that this factor could act as a biomarker for SCA3.